A power cycling degradation inspector of power semiconductor devices. (September 2018) - Watanabe, A.; Omura, I.
Abstract: We have proposed a failure analysis based on a real-time monitoring of power devices under acceleration test. The real-time monitoring enables to visualize the mechanism that leads to a failure by obtaining the change of structure inside the device in time domain with high spatial resolution. In this paper, we presented a new analytical instrument based on the proposed failure analysis concept. The essential functions of this instrument are (1) power stress control, (2) non-destructive inspection and (3) water circulation. An original design power-stress control system and a customized scanning acoustic microscopy system enable us a non-destructive inspection inside the device under power cycling test. This instrument exhibits a great advantage especially to monitor failure mechanisms without having to open the module. Highlights: A failure analysis based on real-time monitoring of power devices under acceleration test Present a new analytical instrument based on the proposed failure analysis concept Combining an original design power-stress control system and a customized SAM system